Impact of vaccination strategy adjustments on antibody levels against measles, rubella, mumps, and varicella in China: a single-center serological survey - Geng, Zhixin; Wang, Wen; Zhu, Yuanyuan; Xu, Yan; Chen, Qiang; Zhang, Lei; Yu, Jing; Sun, Xiang; Wang, Zhiguo (Frontiers in Immunology, 2025)
ObjectiveThis study evaluated trends in population immunity against measles, rubella, mumps, and varicella in Suqian City (2005–2024) using serological surveys (2019–2024) and incidence data, incorporating participants with known/unknown vaccination statuses to explore immunity dynamics amid evolving policies, and inform public health planning.MethodsSerum samples from 541 (2019) and 506 (2024) healthy participants were analyzed for virus-specific IgG antibodies using ELISA. Disease incidence data were obtained from China’s National Notifiable Disease Reporting System. Statistical analyses compared seroprevalence, geometric mean concentrations (GMCs), and incidence trends before and after policy adjustments.ResultsOptimized two-dose strategies significantly improved seropositivity rates for rubella (65.1% to 70.8%), mumps (77.6% to 85.8%), and varicella (76.9% to 79.5%), with corresponding GMC increases. Incidence declines were notable: varicella (183.3/100,000 to 59.3/100,000), rubella (2.8/100,000 to 0.04/100,000), and mumps (24.4/100,000 to <5.0/100,000). However, measles seropositivity declined from 85.9% to 79.3% (p<0.05). GMC analysis showed increases for rubella (31.5 to 42.2 IU/ml), mumps (277.8 to 350.6 IU/ml), and varicella (295.9 to 309.8 IU/ml), but a decrease for measles (577.9 to 499.2 mIU/ml, p<0.001). Preschool children (2–5 years) exhibited the highest immunity levels in 2024.ConclusionPopulation immunity against rubella, mumps, and varicella improved (2019–2024) with reduced incidence, while measles immunity declined, revealing vulnerabilities. Targeted strategies (e.g., catch-up campaigns for adolescents/adults, optimized infant vaccination) are needed to strengthen protection, considering interactions of policies, public health measures, and demographics.